2021
DOI: 10.4049/jimmunol.2001029
|View full text |Cite
|
Sign up to set email alerts
|

Targeting In Vivo Metabolic Vulnerabilities of Th2 and Th17 Cells Reduces Airway Inflammation

Abstract: T effector cells promote inflammation in asthmatic patients, and both Th2 and Th17 CD4 T cells have been implicated in severe forms of the disease. The metabolic phenotypes and dependencies of these cells, however, remain poorly understood in the regulation of airway inflammation. In this study, we show the bronchoalveolar lavage fluid of asthmatic patients had markers of elevated glucose and glutamine metabolism. Further, peripheral blood T cells of asthmatics had broadly elevated expression of metabolic prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…As first shown by Tibbitt et al [ 28 ] and later confirmed by Healey et al [ 29 ], metabolically, in vitro-differentiated Th2 cells were shown to display the highest levels of glycolysis of all T helper cell subsets while also having a high mitochondrial oxygen consumption. Furthermore, Th2 cytokine secretion was shown to be glycolysis-dependent, while ex vivo -isolated BALF Th2 cells from a HDM-mouse model showed no enrichment of genes related to glycolysis [ 28 ].…”
Section: Cell Type-specific Findings In Allergymentioning
confidence: 68%
See 1 more Smart Citation
“…As first shown by Tibbitt et al [ 28 ] and later confirmed by Healey et al [ 29 ], metabolically, in vitro-differentiated Th2 cells were shown to display the highest levels of glycolysis of all T helper cell subsets while also having a high mitochondrial oxygen consumption. Furthermore, Th2 cytokine secretion was shown to be glycolysis-dependent, while ex vivo -isolated BALF Th2 cells from a HDM-mouse model showed no enrichment of genes related to glycolysis [ 28 ].…”
Section: Cell Type-specific Findings In Allergymentioning
confidence: 68%
“…Activated T cells increase their uptake of glutamine and lack of glutamine was shown to impair both their cytokine secretion and proliferation [ 27 ]. In 2021, Healey et al analyzed the bronchoalveolar lavage fluid (BALF) of asthmatic patients and found hints of a generally enhanced metabolism (as shown by higher lactate concentrations after allergen challenge) and markers for both increased glycolysis and glutamine metabolism [ 29 ]. In mice sensitized to Alternaria alternate extract, enhanced OxPhos, glucose, and glutamine metabolism were observed in both Th2 and Th17 cells, while Th17 cells also had a higher potential for glutamine metabolism [ 29 ].…”
Section: Cell Type-specific Findings In Allergymentioning
confidence: 99%
“…It has been reported that GLS‐1 mediated glutaminolysis contributes to psoriasis pathogenesis through the induction of Th17 and γδ Th17 cell differentiation, but not Th1 cell or iTreg differentiation (Xia et al, 2020). Effectors Th2 and Th17 cells promote inflammation in asthmatic patients and analysis of bronchoalveolar lavage fluid of asthmatic patients had shown elevated markers of glucose and glutamine metabolism which supports Th1 and Th17 cell differentiation (Healey et al, 2021). As we know Th17 cells rely on de‐novo synthesis of fatty acids, it was demonstrated that mice fed with high trans fatty acids exhibited higher Th17 cells and ROR‐γt expression with increased Th17 response which develops colitis and other inflammation in response to dextran sodium sulfate (Berod et al, 2014; Okada et al, 2013).…”
Section: Cd4+ T Cell Effector Subsetsmentioning
confidence: 98%
“…Eosinophil-derived major basic protein operates as an antagonist of M2AchR, inhibiting the negative feedback loop and potentiating oversecretion of ACh that leads to bronchoconstriction in the lungs [22]. L-Glu has been reported to increase in eosinophils upon hyper-responsiveness of the unified airway [41]. Histamine [42] and NMU [59] stimulate eosinophil migration, NGF promotes the activation and degranulation of eosinophils [18], whereas adenosine inhibits their accumulation at the inflammatory sites [89].…”
Section: Neuronal-eosinophil Unitmentioning
confidence: 99%